PENGARUH PROGRAM KERJA MAHASISWA KAMPUS MENGAJAR TERHADAP PENINGKATAN LITERASI DAN NUMERASI SISWA DI SDN 1 SONGO - Bagas Permana Putra; Hanif Krisna Adhiansyah; Alvina Hermawaty; Amanda Putri Elysia; Vinna Ariyani; Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Education is an important institution for developing superior human resources and improving their quality. Today's educational demands not only give students a competitive advantage, but also equip them to face future challenges that will play a role in changing society for the better. Freedom to Learn, Independent Campus has become the slogan of education in Indonesia. The campus teaching program established by the government is one of the aims of developing and achieving prosperous education. One of the superior programs in campus teaching activities is numeracy literacy. There is great hope that this program will be able to improve abilities and apply the concept of numbers and arithmetic operations in everyday life as well as interpreting quantitative information in the environment. The aim of this research is to see how effective the numeracy literacy program is, which has long been seen as a superior program for campus teaching activities. This research uses a descriptive qualitative approach with a case study method. The increase in AKM numeracy test results after implementing the program shows the effectiveness of numeracy activities carried out in a structured manner, such as the use of mathematics TTS and digital-based numeracy activities. Students are actively involved in solving math problems appropriate to their grade level, including game elements that attract their attention. However, for literacy, it appears that the AKM literacy test scores remained stable after the program was implemented.